Preferences in Costa Rica for purchasing fruits and vegetables through e-commerce - Villalobos Monge, Alexis (2024)
The objective of this study was to analyze the case of the Costa Rican population regarding the consumption and purchasing preferences of fruits and vegetables, with e-commerce being one of the alternative channels for acquiring these food items. A questionnaire consisting of forty questions was administered to 388 purchasing individuals at eight Farmers' Markets located in the Greater Metropolitan Area (GAM) during the period from May 21 to July 24, 2022. The data was modeled using confirmatory factor analysis and evaluated using structural equation modeling to assess the causal relationships among the variables in the model. The main findings of the research revealed that individuals with a greater inclination towards purchasing food through ecommerce have an intention to purchase larger volumes of fruits and vegetables compared to those who prefer other physical shopping channels such as supermarkets. The COVID-19 pandemic resulted in an approximate 40 % increase in the consumption of these products among the country's population.